ANDROID-BASED DECISION SUPPORT SYSTEM TO DETERMINE APPROPRIATE TIME FOR RICE CULTIVATION IN AGRICULTURAL LAND OF CENGKLIK RESERVOIR - Yusuf Sulistyo Nugroho; Aldo Brian Granada (Jurnal Teknik Informatika (Jutif), 2022)
Cengklik Reservoir is one of the tourism places in Ngemplak, Boyolali Regency, Central Java. This strategic location does not only attract the tourists to visit but is also used by farmers as a source of irrigation for their rice fields. The use of farmland around the Cengklik Reservoir as agricultural land can reduce the problem of drought which has been rarely encountered by farmers. However, another problem arises when the water in the reservoir overflows due to the increased rainfall. This can result in potential damage to paddy fields and might cause crop failure. This study aims to develop the Agraria, an Android-based Decision Support System (DSS) to inform an appropriate period of time for farmers to cultivate crops so that can reduce the risk of crop failures. The system was developed by applying the Mamdani Fuzzy Logic method to process the data taken from public data on weather forecasts of the Meteorology, Climatology and Geophysics Agency (BMKG). The results of the study show that the Android-based decision support system has been successfully developed. The accuracy test was carried out 10 times with an average value of 98.85%. This indicates that the system can be used to help farmers determine the appropriate time for planting so as to avoid the crop failure in the future.